Serviços informacionais via Web [manuscrito] : conjuntura atual da biblioteca central da Universidade Estadual da Paraíba - Silva, Fernanda Mirelle de Almeida (2010)
Today the services offered by information units, more specifically the Academic Libraries, compose a great differential with the introduction of information technology in library services, which benefits professionals of this niche and users of such services. With this perception, a research was held aiming to identify the use of information services on the Web, offered by the Central Library at Paraiba s State University (BC/UEPB), to the students of Master in Environmental Science and Technology (MCTA). This is an exploratory study of quantitative and qualitative nature. The sample is composed of 49 users. To collect data a questionnaire was applied to users of the Central Library of UEPB and a form was applied to eight directors of Central Libraries of State Universities in the Northeast of Brazil, in order to compare the Web information services offered by BC/UEPB with the ones offered by academic librarians of universities located in the Brazilian Northeast. Data analysis shows that the Web information services offered by the Academic Libraries of State universities in the Brazilian Northeast, in general, present a worrying picture. On one hand, some libraries have not yet implemented that kind of services and, in the other hand, those libraries that already offer them, need a better structure. In this scenario 12.5% of Central Libraries are not computerized and do not have websites, respectively. It can be concluded that, at this moment, on-line information services is not part of the reality of some Central Academic Libraries of State Universities in the Brazilian Northeast. However, comparing the study with other studies on the information services on Web, provided by academic libraries, in general, the realities do not differ significantly.